EFEK PERLAKUAN FREEZE-THAW TERHADAP SIFAT-SIFAT MEMBRAN GELATIN-CARBONATED HYDROXY APATITE SEBAGAI PERANCAH DALAM REGENERASI SARAF - , Arum Patriati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One of the major challenges in the development of scaffold for nerve regeneration is enhancing mechanical strength of the material to avoid the scaffold to rapidly degrade during regeneration process in nerve system. The aim of this study was to reveal the effect of freeze-thaw to the properties of gelatin-carbonated hydroxy apatite (CHA) membrane in two ratios 7 to 3 and 6 to 4 for gelatin to CHA respectively. Some variations of freeze-thaw cycles were applied for both ratios, which is known for its biocompatibility in cells. The CHA was synthesized by wet precipitating method of calcium hydroxide and phosphoric acid in gelatin solution at room temperature and open system. The X-Ray Diffraction (XRD) and FTIR analysis was conducted to confirm the formation of type-B CHA in gelatin matrix. The resulted membrane was then subject for membrane characterization. It was known from the study that freeze-thaw treatment during membrane fabrication affects several properties of the membrane. Platelet loading capability decreased when freeze-thaw cycles increased. Meanwhile, the platelet was released more rapidly by freeze-thawed gelatin-CHA membrane compared to non-freeze-thawed one. The degradation percentage of the membrane decreased with the increasing freeze-thaw cycles, showing 4 hours slower degradation in the freeze-thawed membrane compared to the unfreeze-thawed one. Furthermore, it was observed that freeze-thaw improved the tensile strength of the membrane, although the modulus elasticity increased simultaneously. Moreover, in general it was observed from this study that freeze-thaw treatment did not affect permeability of the membranes towards glucose transport.